PENERAPAN PRINSIP GOOD GOVERNANCE DALAM PENGELOLAAN BADAN USAHA MILIK DESA KOTORAJO KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI TAHUN 2020 - Elga Febriyandi Fahmilia Putri; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to explain the application of the principles of good governance in the management of the New Spirit BUMDes. This study focuses on the principles of Cooperative, Emancipatory, Participatory, Transparency and Accountability. This research is a qualitative research. This study uses primary data and secondary data obtained from relevant and competent parties and is directly involved in the establishment and management of the New Spirit BUMDes. The stages of data analysis in this study include interviews, data collection, classifying data, presenting data and drawing conclusions. The results of the study show that the application of the principles of Good Governance in Village-Owned Enterprises (BUMDes) New Spirit with the principles of Participation, the Rule of Law, Transparency and Accountability has been implemented quite well, although there are principles that must be evaluated, and there are several factors that hinder performance in BUMDes management. Lack of facilities and infrastructure and weak human resources in BUMDes. Weak human resources can be seen from the education of BUMDes managers, who on average graduate from junior high/high school, BUMDes and the lack of skills and experience of BUMDes members. this is what the BUMDes manager still needs to evaluate and so that they can provide training for BUMDes managers. Keywords: Participation, Rule of Law, Transparency, Accountability